Intra-Industry Trade of Arab Countries : An Indicator of Potential Competitiveness - Kunzel, Peter; Havrylyshyn, Oleh. (Washington, D.C. : International Monetary Fund, 1997)
Recent and ongoing agreements to liberalize trade between the European Union (EU) and Arab countries raises the question as to how the latter will fare in a more competitive environment. This paper uses the Grubel-Lloyd intra-industry trade (IIT) index as an indicator of the degree of industrial specialization to study Arab countries' ability to compete in a more open trade setting. It concludes that whereas increased specialization has been achieved over the last decade in Arab countries, IIT remains low not only in absolute terms, but even in a cross-country comparison, when normalized for the level of development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet